WORKSHOP METODOLOGI PENELITIAN ILMIAH BAGI MAHASISWA STIT MUARA ENIM - Muhammad Sirozi; Fitri Oviyanti; Muhamad Afandi; Firmansyah (Bahasa Indonesia, 2023)
This community service is carried out at STIT Muara Enim in the form of a workshop, which aims to increase students' understanding of scientific research methodology. The target to be achieved through this activity is to increase the skills of STIT Muara Enim students in compiling thesis writing, as a student's final project. The implementation of the workshop is divided into four stages, namely: 1) the preparation stage, 2) the implementation stage, 3) the evaluation stage, and 4) the reporting stage. This activity went well and smoothly in accordance with the stages arranged in the schedule for the implementation of the activity. This can be seen from the achievement of the training objectives and enthusiasm, as well as the activeness of the participants in the workshop activities. The results achieved through this workshop are very significant towards increasing the understanding of STIT Muara Enim students towards the methodology of writing scientific papers, which positively indicates an improvement in student skills in compiling thesis writing. The results of the evaluation of this activity show that there are several factors that support the implementation of the activity, namely: 1) the existence of good cooperation and full support from partners related to the provision of facilities and infrastructure; 2) the existence of procedures in the implementation of workshop activities; and 3) the enthusiasm of the participants in participating in the workshop activities. In addition to these supporting factors, there are also factors that hinder the implementation of activities, namely limited activity time that cannot satisfy all participants present. Abstrak Pengabdian kepada masyarakat ini dilaksankan di STIT Muara Enim dalam bentuk workshop, yang bertujuan untuk meningkatkan pemahaman mahasiswa tentang metodologi penelitian ilmiah. Target yang ingin dicapai melalui kegiatan ini yaitu meningkatnya keterampilan mahasiswa STIT Muara Enim dalam menyusun penulisan skripsi, sebagai tugas akhir mahasiswa. Pelaksanaan workshop dibagi dalam empat tahap, yaitu: 1) tahap persiapan, 2) tahap pelaksanaan, 3) tahap evaluasi, dan 4) tahap pelaporan. Kegiatan ini berjalan dengan baik dan lancar sesuai dengan tahapan-tahapan yang disusun dalam jadwal pelaksanaan kegiatan tersebut. Hal ini terlihat dari ketercapaian terhadap tujuan pelatihan dan antusiasme, serta keaktifan peserta dalam kegiatan workshop. Hasil evaluasi terhadap kegiatan ini menunjukkan bahwa terdapat beberapa faktor yang mendukung terlaksananya kegiatan, yaitu: 1) adanya kerja sama yang baik dan dukungan penuh dari mitra terkait penyediaan sarana dan prasarana; 2) adanya prosedur dalam pelaksanaan kegiatan workshop; dan 3) antusiasme peserta dalam mengikuti kegiatan workshop. Di samping faktor pendukung tersebut, terdapat juga faktor penghambat pelaksanaan kegiatan, yaitu keterbatasan waktu kegiatan yang tidak dapat memuaskan semua peserta yang hadir. Hasil yang dicapai melalui workshop ini sangat signifikan terhadap peningkatan pemahaman mahasiswa STIT Muara Enim terhadap metodologi penulisan karya ilmiah, yang secara positif berindikasi pada peningkatan keterampilan mahasiswa dalam menyusun penulisan skripsi.